The Effect of The Match Results on Bali United's Stock Price Movements - Agung Novianto Margarena; Arian Agung Prasetiyawan (Relevance: Journal of Management and Business, 2020)
This study was conducted due to differences in the study results in several countries related to the effect of the match results on stock movements. Dimic et. al (2019) stated the match results effect the movement of stock prices, while Mishra & Smyth (2010) stated the vice versa. Then, Floros (2014) put forward different results through the study of four clubs in four European countries. Thus, this study reexamines the effect of the match results on the stock price movement of Bali United. Moreover, Bali United is the first Southeast Asian football club to be listed on the stock market. This study uses a quantitative method with a sample of 31 Bali United’s matches after listed on the stock market. The data were analyzed using simple linear regression with SPSS 21 with either won, drawn or lost match results represented by goal margins. The stock price movements are represented by stock prices after the results of the match. It was found that the results of the match had a positive effect on the stock movement of Bali United.